Determinación mediante pcr en tiempo real de Salmonella sp. y ADNr 16S bacteriano en muestras de alimentos de los establecimientos adyacentes a la Universidad Politécnica Salesiana Quito, sector El Girón - Echeverría Torres, Andrea Estefanía (2015)
Progress in biotechnology has allowed the development of molecular techniques such as Real Time PCR, which is a standard technique used for quantification of both DNA and mRNA in a test sample by identifying the gene and expression of specific sequences. This technique provides a large amount of data with high sensitivity and speed using modern platforms that prevent pollution that can be caused by nucleic acids in the laboratory. Using this technique it has been possible to detect food immediately pathogens as Salmonella sp. in small amounts can cause gastroenteric diseases resulting dangerous to the health of consumers.